2007
DOI: 10.3928/00989134-20070301-03
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility Accommodations for Older Adults Seeking e-Health Information

Abstract: <h4></h4> <p>The study tested the effect of Web page design accommodations for older adults. Two websites, designed by the researchers, were viewed and evaluated by three groups of adults: Younger (ages 30 to 64), Older (ages 65 to 84), and Oldest (ages 85 and older). The two sites, one with accommodations and one without, had identical health content. Thirty adults in each of three age groups rated both web pages. A 2 X 3, mixed ANOVA, age by page style was calculated. Both main effects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…There have been many studies that have analyzed the benefits of Internet use and the ICT for older adults, and how these technologies can meet their needs. This literature shows that digital technology helps older adults communicate with their families and friends [44], widen their permanent learning opportunities [11], allows access to information related to health [10], and helps in exploring resources to satisfy their personal and entertainment needs [19,57]. In summary, digital technology can improve the quality of life of older adults [7] and can help older adults in their daily routines [39].…”
Section: The Use Of Technology For Active Ageingmentioning
confidence: 99%
“…There have been many studies that have analyzed the benefits of Internet use and the ICT for older adults, and how these technologies can meet their needs. This literature shows that digital technology helps older adults communicate with their families and friends [44], widen their permanent learning opportunities [11], allows access to information related to health [10], and helps in exploring resources to satisfy their personal and entertainment needs [19,57]. In summary, digital technology can improve the quality of life of older adults [7] and can help older adults in their daily routines [39].…”
Section: The Use Of Technology For Active Ageingmentioning
confidence: 99%
“…Similarly, Stewart and colleagues 4 found that women compared to men in a coronary care unit wanted more information about angina, high blood pressure, and overall, were not as satisfied with their health‐care providers meeting their informational needs compared to men. Additionally, studies have demonstrated that women with coronary heart disease suffer poorer health status, experience more difficulty returning to daily functioning, and express more psychosocial problems than do men, 25–28 which may also highlight the women in this study expressing preferences for a support group with fellow ICD recipients and a professional counselor.…”
Section: Discussionmentioning
confidence: 74%
“…The differences in age preferences seen here is consistent with other research. Younger individuals are more avid users of computers and the Internet, and recent research has been pursuing methods for involving older adults in computer and Internet interventions 28–31 . Data from Pew Internet Research report that older Americans are the fastest growing segment of Internet users and that more than one‐third of Americans over the age of 64 years will be online as of 2008 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Past nursing and caring literature has studied and described how the use of different technological tools affects patients' experiences of illness [11,12], patients' experiences of getting information from health care personnel or websites [13][14][15], how technical tools fit in the nursing purposes, such as patients' follow-up services [16,17], or how the technical tools affect patients' coping skills compared to traditional support and educational methods [18]. The focus of the studies has been on illness, i.e., other that the patients' experiences of technology and its use in their care.…”
Section: Related Literaturementioning
confidence: 99%